Association between smoking status assessed with plasma‐cotinine and inflammatory and endothelial biomarkers in HIV‐positive and HIV‐negative individuals. Issue 10 (9th July 2018) - Ahlström, MG; Knudsen, A; Ullum, H; Gerstoft, J; Kjaer, A; Lebech, A‐M; Hasbak, P; Obel, N
Abstract : Objectives: Smoking is a major contributor to mortality and morbidity in HIV‐positive individuals. Our primary objective was to evaluate the association between smoking status determined by plasma cotinine (P‐cotinine) concentration and inflammatory and endothelial biomarkers in HIV‐positive versus HIV‐negative individuals. Methods: We studied eight inflammatory/endothelial biomarkers [high‐sensitivity C‐reactive protein (hsCRP), E‐selectin, soluble vascular cell adhesion molecule 1 (sVCAM‐1), soluble intercellular adhesion molecule 1 (sICAM‐1), matrix metallopeptidase 9 (MMP‐9), myeloperoxidase (MPO), tissue type plasminogen activator inhibitor 1 (tPAI) and endothelin] in 105 HIV‐positive individuals and 105 HIV‐negative individuals matched on age, sex and self‐reported smoking status. Smoking status was determined using P‐cotinine (a concentration > 14 ng/mL was defined as demonstrating exposure to smoke). We used linear regression models to (1) examine the association between smoking status and inflammatory/endothelial biomarkers in HIV‐positive compared with HIV‐negative individuals, and (2) to determine whether there was evidence to suggest that the impact of smoking status on the biomarkers differed between HIV‐positive and HIV‐negative individuals. Results: Of the eight biomarkers, smokers had increased hsCRP, sICAM‐1 and MMP‐9 concentrations irrespective of HIV status and increasing P‐cotinine concentration was associated with increasing hsCRP concentration. We found no interaction between smoking and HIV status. HIV infection was associated with increased hsCRP, E‐selectin, sVCAM‐1, sICAM‐1 and MMP‐9 concentrations. Self‐reported smoking status differed substantially from smoking status assessed with P‐cotinine. Conclusions: Several biomarkers were associated with smoking status and HIV status. However, our data do not indicate that the effects of smoking on the biomarkers differ between HIV‐positive and HIV‐negative individuals.